(untitled) (Kinesiology, 2024)
This study aimed to compare the collective and individual tactical positional behavior before the first goal was scored or conceded in official soccer matches. The sample comprised 50 players and 27 official matches played in Brazil during the 2020 and 2021 U-20 seasons. Global Positioning System devices were used to monitor the players’ positional data. Collective – width, length, length per width ratio, and stretching index, and individual – spatial exploration index, variables were calculated and compared between the contextual scenarios by a one-way ANOVA. Results indicated a reduction in the width after scoring a goal (p=.006) and a lower spatial exploration after conceding a goal (p<.001) compared with the draw condition. Therefore, it is concluded that goal-scoring affects the tactical positional responses of the players. Specifically, a higher width concentration, characteristic of defensive tactical behavior, is observed after scoring a goal to keep the current match status. On the other hand, players present difficulties in exploring the space after conceding a goal. The knowledge of these intrinsic game dynamics is helpful for coaches in preparing the strategies to explore changes due to goal scoring in official matches. Keywords: football, youth sport, GPS devices, ecological dynamics